A new species of Leielmis Delève, 1964, with a revised key to members of the genus (Coleoptera: Elmidae) - Bilton, David T. (Zootaxa, 2018)
The genus Leielmis was recently revised by Bilton (2017), who established the identity of the type species Leielmis georyssoides (Grouvelle, 1890), and described two new taxa: Leielmis gibbosus Bilton, 2017, widespread in the Cape Fold Mountains and Leielmis hirsutus Bilton, 2017, known to date only from a single site at high altitude in the Groote Winterhoek mountains. A distinctive new species of Leielmis was discovered in a high altitude stream in 2017 in the Hexrivierberge, being collected whilst the generic revision was in press! This species is described below, and a modified key to Leielmis species presented. In light of this discovery it appears likely that further work at high altitude will reveal additional species in the Cape.